Acute effects of mat Pilates session on heart rate and rating of perceived exertion - Ramos do Espirito Santo, Barbara Carlin de; Garcias, Leandro; Bertoli, Josefina [UNESP]; Kulevicz da Silva, Affonso Celso; Freitas, Cintia de la Rocha (Elsevier B.V., 2020)
Aims: The aim of this study was to analyze the acute effects of Heart Rate (HR) and Rating of Perceived Exertion (RPE) for 21 of 34 original Mat Pilates (MP) exercises, to estimate maximum oxygen consumption (VO2max), and energy expenditure (EE) of a MP session. Methods: Ten participants volunteered (26.30 +/- 3.98 yrs) to measure the intensity of each exercise; HR and RPE were monitored immediately after the end of each exercise. VO(2max)was estimated using the Astrand-Ryhming step submaximal test, and EE by a linear regression equation. HR and RPE mean values and standard deviations were calculated for each exercise. Results: The maximum value for each participant normalized the EE and VO2max values, which were ranked from highest to lowest. The percentage of the mean values of HRmax and RPEmax in each exercise showed significant, strong and positive correlation (p = 0.82; p = 0.001). In 10 exercises, HR was 60% higher than HRmax. The mean values of EE and VO2max were 213.71 +/- (76.41) Kcal and 34.69 ml (Kg.min)(-1) (+/- 3.5), respectively, for the entire MP session. Half of the exercises achieved moderate intensity in HR with low estimated VO2max during the whole MP session. However, if the MP session of this study was practiced five times per week, it would meet the weekly American College of Sports Medicine (ACSM) EE recommendations. Conclusion: The 21 MP exercises monitored in this study promote considerably acute and high increments in HR and RPE. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Energy expenditure; Maximum oxygen consumption; Exercise intensity; Mat pilates; Heart rate